What works in inclusion health: overview of effective interventions for marginalised and excluded populations. Issue 10117 (20th January 2018) - Luchenski, Serena; Maguire, Nick; Aldridge, Robert W; Hayward, Andrew; Story, Alistair; Perri, Patrick; Withers, James; Clint, Sharon; Fitzpatrick, Suzanne; Hewett, Nigel
Summary: Inclusion health is a service, research, and policy agenda that aims to prevent and redress health and social inequities among the most vulnerable and excluded populations. We did an evidence synthesis of health and social interventions for inclusion health target populations, including people with experiences of homelessness, drug use, imprisonment, and sex work. These populations often have multiple overlapping risk factors and extreme levels of morbidity and mortality. We identified numerous interventions to improve physical and mental health, and substance use; however, evidence is scarce for structural interventions, including housing, employment, and legal support that can prevent exclusion and promote recovery. Dedicated resources and better collaboration with the affected populations are needed to realise the benefits of existing interventions. Research must inform the benefits of early intervention and implementation of policies to address the upstream causes of exclusion, such as adverse childhood experiences and poverty.